2016
DOI: 10.1002/vnl.21533
|View full text |Cite
|
Sign up to set email alerts
|

Properties and characterization of ([Mengkuang leaf fiber]‐filled ethylene vinyl acetate)/(natural rubber) blend: Effects of blending sequences and mengkuang leaf fiber loading

Abstract: Ethylene vinyl acetate [EVA])/(natural rubber [NR])/ (Mengkuang leaf fiber) (MLF) thermoplastic elastomer composites were prepared by using three different blending sequences in an internal mixer. The blending sequences studied were (i) B1: NR was added followed by MLF into the molten EVA; (ii) B2: MLF was added followed by NR into the molten EVA; (iii) B3: MLF was added followed by EVA into the molten NR. The effect of different blending sequences and fiber loadings from 10 to 40 parts by weight per hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This can be attributed to the increased likelihood of fiber pull-out with higher fiber content. [40][41][42][43][44][45]…”
Section: Tensile Strengthmentioning
confidence: 99%
“…This can be attributed to the increased likelihood of fiber pull-out with higher fiber content. [40][41][42][43][44][45]…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The EVA/NR/ Mengkuang leaf fibre composites were prepared by melt mixing in a Haake Rheomix Polydrive R 600/610 at 120 °C with the rotor speed of 50 rpm over a constant mixing time of 10 min. The blend ratio of NR and EVA was fixed at 50:50 (Ismail et al 2008;Hashim et al 2016). The formulations of the composites are given in Tables 1 and 2.…”
Section: Preparation Of Eva/nr/ Mengkuang Leaf Fibre Tpvs Compositesmentioning
confidence: 99%
“…Among several existing natural fibres, Mengkuang leaf fibre has been selected as a reinforcement in the matrix. Mengkuang is a member of the Pandanaceous family, growing in mangrove swamps and jungles (Hashim et al 2016). Mengkuang leaf fibre has been introduced into the composites as a filler to enhance their processability and mechanical properties, as well as to reduce material costs (Hashim et al 2016;Abdullah and Aslan 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashim et al [20] used thermoplastic elastomer composite of ethylene vinyl acetate (EVA)/natural rubber (NR)/MLF to study the effect of MLF loading (from 10 wt.% to 40 wt.% with an increment of 10 wt.%) on tensile properties. They concluded that an increase in MFL loading resulted in an increase in Young's modulus but a decrease in tensile strength.…”
Section: Introductionmentioning
confidence: 99%